Incidence of Peste des Petits Ruminants in Rangpur sadar of Bangladesh - Rahman, Md Mamunur; Hassan, Md Zakir; Sultana, Salma; Uddin, Md Karim; Hossain, SM Sarwar (Asian Journal of Medical and Biological Research, 2018)
This epidemiological study was conducted to find out the incidence of Peste des Petits Ruminants (PPR) in goat and sheep at Upazilla Veterinary Hospital, Rangpur sadar, Rangpur during the period of January to April, 2014. In this period, 236 clinically infected goat and sheep were examined in which 22 (9.32%) PPR cases were diagnosed on the basis of history, clinical signs and gross pathological lesions. High fever (104-107 oC), mucopurulent oculo-nasal discharge, rapid and labored breathing, mouth lesion and diarrhea were the common clinical sign of PPR infected goat and sheep. The postmortem examination findings were dark red areas and congestion in different lobes of lungs, enlargement of spleen and lymph nodes, erosion of abomasums and characteristics zebra striping in the mucosa of colon. This present study reveals that about 7-12 months aged group of goats were more prone (40.91%) to PPR compare to adult (above 1 year) and Black Bengal goat was more susceptible (72.32%) than Jamunapari (27.78%) goat where the occurrence of PPR disease was more in goat (81.82%) than sheep (18.18%). Asian J. Med. Biol. Res. December 2017, 3(4): 529-533